1982
DOI: 10.1007/bf01887644
|View full text |Cite
|
Sign up to set email alerts
|

Patient radiation doses in upper GI examinations: A comparison between conventional and double-contrast techniques

Abstract: A total of 60 patients, divided into 3 groups with 20 patients in each, were examined with 3 different techniques: group 1 -- conventional technique, exposure at 120 kV; group 2 -- double-contrast technique (hypotonic gastrography, HG), exposure at 80 kW; group 3 -- HG, exposure at 120 kV. All examinations were performed in the same examination room and by the same radiologist. Absorbed doses to skin, thyroid, breasts, and gonads as well as energy imparted were measured. The only significant dose enhancements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…As these neonates and younger children have some degree of physiologic reflux and are sometimes maneuvered to elicit reflux, the risk of barium aspiration is also a consideration [2]. In addition, though the radiation exposure to UGIs is relatively low (80-120 kV), cumulative dosing over the life of the patient with other procedures may increase the risk of cancer in these patients [9,10]. In sum, although some surgeons may use UGIs as a screening tool for reflux, the consistency and reliability of the data obtained is questionable.…”
Section: Discussionmentioning
confidence: 98%
“…As these neonates and younger children have some degree of physiologic reflux and are sometimes maneuvered to elicit reflux, the risk of barium aspiration is also a consideration [2]. In addition, though the radiation exposure to UGIs is relatively low (80-120 kV), cumulative dosing over the life of the patient with other procedures may increase the risk of cancer in these patients [9,10]. In sum, although some surgeons may use UGIs as a screening tool for reflux, the consistency and reliability of the data obtained is questionable.…”
Section: Discussionmentioning
confidence: 98%
“…That study used tube potential (kVp), current-time product (mAs), field size, and beam filtration of radiographic machines in 13 Swedish hospitals from 1973 to 1975 and measured radiation doses at various points on 1,000 patients using lithium fluoride (thermoluminescent) dosimeters (Harshaw Chemical Co., Cleveland, OH). The thyroid dose resulting from upper GI fluoroscopy in the 1980s and 1990s were adopted from a study by Bankvall et al (1982) and Suleiman et al (1991) which reported thyroid tissue doses from upper GI series. For the thyroid doses in the 2000s from an upper GI series, we employed average GI series time, number of images, tube potential (kVp), current-time product (mAs), and field size from the Nationwide Evaluation of X-Ray Trends (NEXT) survey reports (CRCPD and FDA 1996, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Outliers are also included in parentheses. b Data extrapolated c Derived from Public Health Service, 1964 d Derived from Bentgsston et al 1978 e Derived from Bankvall et al 1982 f Suleiman et al 1991 g Ramakrishnan and Padmanabhan 2001, Crawley et al 2004 …”
Section: Figurementioning
confidence: 99%